Economic impacts of climate change on two Mexican coastal fisheries: Implications to food security - Alonso Aguilar Ibarra; Armando Sanchez Vargas; Benjamin Martinez Lopez (Kiel Institute for the World Economy (IfW), 2012)
This paper has a two-fold objective. First, to estimate the changes in landings value by 2030 of two Mexican coastal fisheries: shrimp and sardines as a consequence of climate change. And second, to discuss the implications for food security of such impacts. We estimated output equations using a dynamic panel model for the Mexican fisheries sector with data from 1990 through 2009. Scenarios were generated for the expected changes in fish production. Our results suggest that shrimp production will be negatively affected in about 1.1% in decreasing catch for every 1% of temperature increase by 2030. In contrast, the sardine fishery would benefit by approximately a 4% increase in production for every 1% increase in temperature. For the shrimp fishery, losses amount from US 95 million (discount rate = 4%) to US 444 million (discount rate = 1%). For the sardine fishery, gains range from US 46 million (discount rate = 4%) to US 184 million (discount rate = 1%). Most losses/gains would be observed in the NW Mexican Pacific, where the fishing sector has an important role in the local economy and represents therefore a risk to food security on a local basis.
Keywords: Q51; C23; Q22; Q54; 330; monetary estimation; climate change; Mexico; shrimp fishery; sardine fishery; food security